Pengendali Suhu dan Kelembaban Berbasis Mikrokontroler Atmega 8535 pada Kumbung Jamur Tiram - Muhammad Akbar Setiawan; Nahar Mahardiyanto; Adnan Purwanto (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2020)
Oyster mushroom is a food mushroom, has a morphology with hood like oyster shells, with the middle slightly concave and white to cream coloured. A necessary condition for the mushroom to grow up is by keeping the temperature and humidity. The condition of temperature and humidity that have to fulfilled for the oyster mushroom is 20 – 30 °C for temperature and 80 % minimum humidity. The temperature and humidity in the mushroom house can’t be known without the measurement tools. This measurement tools that only measure the temperature and humidity in the mushroom house and controlling of the temperature and humidity is always manually. These weaknesses is attempt to overcome by the researcher by develop the temperature and humidity controller device based microcontroller. This device is develop for facilitate the farmer within the controlling of temperature and humidity inside the mushroom house. This device function is to provide a service an output like to blow the blower and spraying water for humidity increasing. After build and tested, this device has been fill the test of dimension of quality for product, and got the 89,5 score for the product test. This is passed the minimum score for the product test, when the researcher was decide the minimum score for the product test was 75.